MENGINTEGRASIKAN LIFE SKILLS KE DALAM MODEL LATIHAN BOLA BASKET DALAM RANGKA POSITIVE YOUTH DEVELOPMENT BERDASARKAN GENDER DAN KATEGORI USIA SEKOLAH - I Kadek Suardika, - (2023)
This research is based on the results of previous research related to the concept of integrated life skills applied in golf. This becomes a thought for researchers to implement the concept of integrating life skills into the basketball training model. The purpose of this study was to examine differences in integrated and non-integrated basketball training models on the development of life skills in terms of gender and school-age categories. The method used in this study is an experimental method with a pretest-posttest control group design. The instrument used is the Life Skills Scale for Sport (LSSS). This study took a sample of 106 athletes who took part in basketball practice. The sample was divided into two groups which were given life skills integration and life skills non-integration treatment. The results showed that the development of life skills in groups following the basketball training model were given better treatment compared to no life skills integration treatment, based on gender, men and women did not experience significant differences in the development of life skills because they had strong and developed characters. simultaneously when using a structured design, based on the school age category in the integration group all levels of education experienced the development of better life skills. It can be concluded that basketball sports activity is a good means to develop life skills through an intentional structure and the principle of integration optimally developed as a provision for our young generation to continue to be able to compete in this globalization competition.